1993
DOI: 10.1007/bf00844820
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of adherence and control in diabetes

Abstract: This study aims to predict adherence to diabetic treatment regimens and sustained diabetic control. During two clinic visits that were 2 months apart, 63 adult outpatients completed measures of diabetic history, current treatment, diabetic control, adherence, and self-efficacy about adherence to treatment. Results showed that self-efficacy was a significant predictor of later adherence to diabetes treatment even after past levels of adherence were taken into account. Posttest levels of adherence in turn were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
88
1
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(95 citation statements)
references
References 19 publications
3
88
1
3
Order By: Relevance
“…Previously, dental self-efficacy has been found to relate to oral hygiene practices and dental visiting (McCaul et al 1985, Tedesco et al 1994, Stewart et al 1997) and, correspondingly, diabetes self-efficacy to diabetes self-care (Hurley & Shea 1992, Littlefield et al 1992, Kavanagh et al 1993. The results of the present study are accordant with these findings concerning health behavior and, furthermore, the relation found here between diabetes self-efficacy and metabolic balance is parallel to that reported by Kavanagh et al (1993) and Day et al (1996).…”
Section: Self-efficacysupporting
confidence: 89%
See 1 more Smart Citation
“…Previously, dental self-efficacy has been found to relate to oral hygiene practices and dental visiting (McCaul et al 1985, Tedesco et al 1994, Stewart et al 1997) and, correspondingly, diabetes self-efficacy to diabetes self-care (Hurley & Shea 1992, Littlefield et al 1992, Kavanagh et al 1993. The results of the present study are accordant with these findings concerning health behavior and, furthermore, the relation found here between diabetes self-efficacy and metabolic balance is parallel to that reported by Kavanagh et al (1993) and Day et al (1996).…”
Section: Self-efficacysupporting
confidence: 89%
“…There has been an association between high diabetes self-efficacy concerning the major diabetes self-care practices and a good level of adherence to those practices (Littlefield et al 1992). It has similarly been found that self-efficacy is associated with diabetes adherence (Kavanagh et al 1993, Lo 1998 and is able to predict glycosylated haemoglobin levels (Kavanagh et al 1993, Day et al 1996. High diabetes self-efficacy has been related to better perceived health, mental health and social functioning (Aalto et al 1997).…”
Section: Self-efficacymentioning
confidence: 96%
“…According to the self-efficacy theory of Bandura (1988), self-efficacy beliefs entail a positive estimation of one's skills and are resistant to change in the face of difficulties, thus sustaining perseverant efforts to attain one's goals (Bandura, 1988;Maddux and Lewis, 1995). In line with the theory, positive efficacy expectancies have been shown to be stable across time in a number of chronic diseases, such as diabetes mellitus (Kavanagh et al, 1993), multiple sclerosis (Barnwell and Kavanagh, 1997), and rheumatoid arthritis (Taal et al, 1993).…”
mentioning
confidence: 63%
“…The value of self-efficacy in predicting self-care behaviors and outcomes in patients with diabetes is supported by several studies, in which self-efficacy was associated with self-reported adherence in adults (3)(4)(5)(6)(7)(8)(9) and adolescents (10,11), glycemic control (8,12,13), and better perceived general health, mental health, and social functioning (14).…”
mentioning
confidence: 95%
“…Several instruments to assess selfefficacy specific to self-care behavior have been used in adult patients with diabetes. In some studies, a single item is used (18); in other studies, data on reliability and validity are lacking (3,8) or not available in English (9). In some cases, the instrument relies heavily on diet-related items (4,15,19) or is concerned with psychosocial issues instead of self-care behavior (20).…”
mentioning
confidence: 99%